Scoring the importance of tropical forest landscapes with local people: patterns and insights - Sheil, Douglas; Liswanti, N. (2006)
Good natural resource management is scarce in many remote tropical regions. Improved management requires better local consultation, but accessing and understanding the preferences and concerns of stakeholders can be difficult. Scoring, where items are numerically rated in relation to each other, is simple and seems applicable even in situations where capacity and funds are limited, but managers rarely use such methods. Here we investigate scoring with seven indigenous communities threatened by forest loss in Kalimantan, Indonesia. The authors aimed to clarify the forest’s multifaceted importance, using replication, cross-check exercises, and interviews. Results are sometimes surprising, but generally explained by additional investigation that sometimes provides new insights. The consistency of scoring results increases in line with community literacy and wealth. Various benefits and pitfalls are identified and examined. Aside from revealing and clarifying local preferences, scoring has unexplored potential as a quantitative technique. Scoring is an underappreciated management tool with wide potential.